Killing two birds with one stone: chemical and biological upcycling of polyethylene terephthalate plastics into food. Issue 2 (February 2023) - Schaerer, Laura G.; Wu, Ruochen; Putman, Lindsay I.; Pearce, Joshua M.; Lu, Ting; Shonnard, David R.; Ong, Rebecca G.; Techtmann, Stephen M.
Abstract : Most polyethylene terephthalate (PET) plastic waste is landfilled or pollutes the environment. Additionally, global food production must increase to support the growing population. This article explores the feasibility of using microorganisms in an industrial system that upcycles PET into edible microbial protein powder to solve both problems simultaneously. Many microorganisms can utilize plastics as feedstock, and the resultant microbial biomass contains fats, nutrients, and proteins similar to those found in human diets. While microbial degradation of PET is promising, biological PET depolymerization is too slow to resolve the global plastic crisis and projected food shortages. Evidence reviewed here suggests that by coupling chemical depolymerization and biological degradation of PET, and using cooperative microbial communities, microbes can efficiently convert PET waste into food. Highlights: Innovative solutions are needed to resolve the ongoing global issues of excess plastic waste and food insecurity. Polyethylene terephthalate (PET) polymers can be depolymerized and biodegraded by naturally occurring microorganisms, although rates of degradation are too slow to independently form the foundation of a biotechnological process and help to resolve the global plastic crisis. Chemical depolymerization of PET can deconstruct plastics into aromatic building blocks. Microorganisms can more rapidly break down the aromatic building blocks of PET after chemical depolymerization, greatly improving rates of biodegradation. Single-cell protein (SCP) is a food source that is derived from microbial cells. Microbial cells grown on waste products offer a promising source of alternative protein and other nutrients.